The Impact of Project-Based Learning Models on Improving Students' Value and Understanding on Natural Sciences Lessons - Maryani, Dwi; Yunianto, Aan; Murtiyasa, Budi; Masduki, Masduki (Bulletin of Science Education, 2023)
In the era of independent learning, there was a low interest in and understanding of Natural Sciences (IPA) subjects among students. The project-based learning model emerged as an alternative to overcoming these constraints. So researchers want to know the impact of project-based learning in primary schools. The method used is pre-experimental quantitative, with the design as follows: taking samples, pretest, providing guidance, post-test after guidance, looking for the average value of the pretest and post-test, and T test results. The research was conducted at Surakarta Basic School with a 30th grade student. Types of bound variables are the values and understanding of students in the V class of Natural Sciences (IPA) and project-based free learning variables. Collecting techniques with post-test and post-test as well as data analysis with pairs of T tests. Research finds that project-based learning models have an influence on elementary school students in the fifth grade in natural science subjects (IPA). Based on the analysis, results show that t hitung > t table (2.977 > 1.6991) means there are significant differences, so the project-based learning model has an influence on value and understanding. Keywords: Impact of Project-Based Learning, Project-Based Learning Models, Improving Students' Value